2018
DOI: 10.1186/s13063-018-3043-3
|View full text |Cite
|
Sign up to set email alerts
|

A cluster randomised trial of a classroom communication resource program to change peer attitudes towards children who stutter among grade 7 students

Abstract: BackgroundClassroom-based stuttering intervention addressing negative peer attitudes, perceptions, teasing and bullying of children who stutter (CWS) is required as part of holistic stuttering management because of its occurrence in primary school. This study was conducted in 2017, in 10 primary schools in the Western Cape, South Africa within lower (second and third) and higher (fourth and fifth) quintiles.ObjectivesThe primary objective of this study was to determine treatment effect at six months after inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
0
16
0
1
Order By: Relevance
“…The details about the Mallick et al study can be found elsewhere [ 5 , 15 ]. In brief, this was a cluster randomized trial aimed at examining the effect of Classroom Communication Resource (CCR) on peer attitude towards Children Who Stutter (CWS) in South African schools in the Western Cape.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The details about the Mallick et al study can be found elsewhere [ 5 , 15 ]. In brief, this was a cluster randomized trial aimed at examining the effect of Classroom Communication Resource (CCR) on peer attitude towards Children Who Stutter (CWS) in South African schools in the Western Cape.…”
Section: Methodsmentioning
confidence: 99%
“…Over the years, the number of adopting CRTs is increasing [ 2 ]. Diverse types of clusters can be allocated in CRTs including: geographical areas [ 3 ]; health care districts [ 4 ]; and schools [ 5 ]. Like trials on individuals’, most CRTs use one of the following three experimental design strategy such as: (a) completely randomized; (b) matched-pair; or (c) stratified.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations